Poultry Production Clusters (PPCs) after AI Outbreaks in Thailand: Past, Present and Future Direction - Aengwanich , Worapol; Intarakhamhaeng, Manakant; Wandee, Jaroon; Nongbua, Tanapol; Chaiyasak, Surangkanang; Srikot, Prayat; Thammasar, Komvut; Junsanitsri, Neti; Sritongtuam, Khlahan; Tawinwaang, Tanat (International Journal of Poultry Science, 2012)
After the outbreaks of avian influenza during the years 2003-2004, Thailand launched many policies to control the spread of the disease such as culling of poultry. Public health measures were also devised to control the transmission of disease to humans and as a result, there was no more report of avian influenza infection in humans after 2007. Based on poultry farming control measure through clustering poultry farms could be classified into 4 groups; namely, poultry farmer communities united before the avian influenza outbreaks, poultry farmer communities united before the avian influenza outbreaks and subsequently implemented cooperative farming system, poultry farmer engaged in contract farming system with large private companies and poultry farmer under compartment system of large private companies. The future direction of these poultry farm clusters should be the improvement of the quality of life of farmers, the promotion of appropriate management and caring of environmental changes, the strengthening of biosecurity, the clustering of farmers within the communities; which would allow farmers in these poultry clusters to have a better quality of life.